Key determinants of academic employees’ performance in Malaysian online distance learning institutions - Zahir Osman,; Loo, Sin Chun,; Raemah Abdullah Hashim,; Norsiah Aminudin,
The objective of this study is to evaluate direct effect of leadership style, employee commitment, organisational culture, self-efficacy and employee performance relationship in Malaysian online distance learning higher institutions (ODL). To analyse the casual relationships among leadership style, employee commitment, organisational culture, self-efficacy and employee performance, the Structural Equation Model (SEM) was adopted. The model was designed and later analysed by using the Partial Least Square (PLS) procedure on data collected from a survey that yielded 206 usable questionnaires. The results showed that leadership style, organisation culture and self-efficacy has a positive and significant influence on academic employees’ performance in Malaysian ODL higher institutions. However, employee commitment did not show significant influence on academic employees’ performance. It is vital to do the research utilising experimental design by using longitudinal data in Malaysian ODL higher institutions via vigorous measures. The findings suggest that ODL institutions should give greater emphasis on strengthening strong and positive leadership style, organiation culture and self-efficacy in ensuring strong performance of their academic employees. [Abstract by authors]